2018
DOI: 10.4254/wjh.v10.i7.485
|View full text |Cite
|
Sign up to set email alerts
|

Balloon-occluded transcatheter arterial chemoembolization for hepatocellular carcinoma

Abstract: Transcatheter arterial chemoembolization (TACE) is widely accepted as a treatment for patients with hepatocellular carcinoma (HCC) in the intermediate stage according to the Barcelona Clinic Liver Cancer (BCLC) guidelines. Recently, balloon-occluded TACE (B-TACE) was developed in Japan. Despite the lack of a clear definition, B-TACE is generally defined as the infusion of emulsion of chemotherapeutic agents with lipiodol followed by gelatin particles under the occlusion of feeding arteries by a microballoon ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
2
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 57 publications
(141 reference statements)
1
41
2
4
Order By: Relevance
“…The Sniper balloon occlusion catheter was also used to regulate flow. Balloon-occluded transcatheter arterial chemoembolization (B-TACE) is an interventional approach that utilizes the infusion of lipiodol (an ethiodized oil) followed by gelatin particles under the occlusion of feeding arteries by a balloon catheter [9]. Using balloon occlusion, the Sniper microcatheter system created a low-pressure gradient at the proximal GDA, forcing blood flow towards the GDA and preventing reflux.…”
Section: Resultsmentioning
confidence: 99%
“…The Sniper balloon occlusion catheter was also used to regulate flow. Balloon-occluded transcatheter arterial chemoembolization (B-TACE) is an interventional approach that utilizes the infusion of lipiodol (an ethiodized oil) followed by gelatin particles under the occlusion of feeding arteries by a balloon catheter [9]. Using balloon occlusion, the Sniper microcatheter system created a low-pressure gradient at the proximal GDA, forcing blood flow towards the GDA and preventing reflux.…”
Section: Resultsmentioning
confidence: 99%
“…This technical bene t should theoretically enhance the ability to locally control tumor growth. Despite this, literature evidence on oncological response of b-TACE over standard non occluded TACE is controversial [3][4][5][6] In order to evaluate the adjunctive value of b-TACE we retrospectively evaluated the results of patients treated in our institution with b-TACE and compared them with an historical cohort treated with non-occluded DEM-TACE. b-TACE and DEM-TACE were performed by the same team under dual phase CBCT guidance i.e..: better tumor/feeders visualization) 15 , with rigorous standardization of the embolization procedure (sequential embolization with 100 and 200 microns particles 12 ), being the only technical variable the balloon micro-catheter employment.…”
Section: Discussionmentioning
confidence: 99%
“…To date there are no randomized controlled trials comparing TACE to b-TACE in terms of oncological response; moreover, some retrospective studies reported con icting results. 3 Ogawa et a l 4 and Irie et al 5 showed a better tumor response for b-TACE performed with Lipiodol in comparison to Lipiodol TACE performed with a standard catheter. Maruyama et al 6 , on the other hand, failed to demonstrate a difference in tumor control between the two techniques.…”
Section: Introductionmentioning
confidence: 96%
“…A good review paper about clinical results of SSLB-TACE is available. 22 Although SSLB-TACE is thought to be a promising technique, randomized prospective controlled trials to compare local control rates with c-TACE are still lacking.…”
Section: Indication Of Sslb-tacementioning
confidence: 99%